2017
DOI: 10.1080/13813455.2017.1388410
|View full text |Cite
|
Sign up to set email alerts
|

A novel biomarker explaining the role of oxidative stress in exercise andl-tyrosine supplementation: thiol/disulphide homeostasis

Abstract: The present study aimed to evaluate the relationship between exercise and both l-tyrosine and oxidative stress using thiol/disulphide homeostasis via a novel biomarker in rats. Following the completion of the exercise and l-tyrosine protocol, serum total thiol, native thiol, and disulphide concentrations were determined using a novel automated measurement method. Compared with the control group, serum dynamic disulphide levels were significantly lower in the E group (116.75 ± 10.49; p < .05) and the highest in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Epileptic seizures are a common feature of mitochondrial dysfunction associated with mitochondrial encephalopathies (Patel, 2004). However, physical exercise has been reported to be effective in the treatment of oxidative stress and impaired brain function that is associated with oxidative stress (Kim et al, 2013;Kayacan et al, 2017). Accordingly, the mid-level running exercise that was performed in the present study reduced epileptiform activity, which may be caused by oxidative stress.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Epileptic seizures are a common feature of mitochondrial dysfunction associated with mitochondrial encephalopathies (Patel, 2004). However, physical exercise has been reported to be effective in the treatment of oxidative stress and impaired brain function that is associated with oxidative stress (Kim et al, 2013;Kayacan et al, 2017). Accordingly, the mid-level running exercise that was performed in the present study reduced epileptiform activity, which may be caused by oxidative stress.…”
Section: Discussionmentioning
confidence: 60%
“…The antioxidant enzyme activity is significantly increased in athletes and exercised rats. The increased antioxidant activity then inhibits lipid peroxidation caused by an exercise-induced increase in oxidative stress (Kayacan et al, 2017;2019). Additionally, individuals exercising regularly have an advantage over sedentary people because training supports the activity of many major antioxidant enzymes and development of the overall antioxidant level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 This novel indicator of oxidative stress was examined in children with simple febrile seizure and the result has shown that the seizure may cause disruption in favor of disulfide bonds. 19 In a previous study, Kayacan et al 20 aimed to evaluate the relationship between exercise and both l-tyrosine and oxidative stress using this new method and the result showed that exercise positively affected thiol/disulphide homeostasis. Moreover, this prognostic biomarker was applied in non small cell lung cancer patient and total thiol, native thiol and disulphide levels was found decreased in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thiols are most important defense system against reactive species due to sulfhydryl groups (SH) in their structure. SH groups can be oxidized by the oxidant molecules in the environment and converted into reversible disulfide (SS) bond structures (11). The disulfide bond structures formed in this way are reduced back to thiol (SH) groups, and the thiol-disulfide balance is preserved (12).…”
Section: Introductionmentioning
confidence: 99%